CD72 polymorphisms associated with alternative splicing modify susceptibility to human systemic lupus erythematosus through epistatic interaction with FCGR2B - Yuki Hitomi (2018)
We previously reported association of FCGR2B-IIe232Thr with systemic lupus erythematosus (SLE) in three Asian populations. Because polymorphism of CD72, another inhibitory receptor of B cells, was associated with murine SLE, we identified human CD72 polymorphisms, tested their association with SLE and examined genetic interaction with FCGR2B in the Japanese (160 SLE, 277 controls), Thais (87 SLE, 187 controls) and Caucasians (94 families containing SLE members). Four polymorphisms and six rare variations were detected. The former constituted two major haplotypes that contained one or two repeats of 13 nucleotides in intron 8 (designated as *1 and *2, respectively). Although association with susceptibility to SLE was not detected, the *1 allele was significantly associated with nephritis among the Japanese patients (P = 0.024). RT-PCR identified a novel alternatively spliced (AS) transcript that was expressed at the protein level in COS-7 transfectants. The ratio of AS/common isoforms was strikingly increased in individuals with *2/*2 genotype when compared with *1/*1 (P = 0.000038) or *1/*2 (P = 0.0085) genotypes. Using the two Asian cohorts, significant association of FCGR2B-232Thr/Thr with SLE was observed only in the presence of CD72-*1/*1 genotype (OR 4.63, 95% Cl 1.47-14.6, P = 0.009 versus FCGR2B-232IIe/IIe plus CD72-*2/*2). Minigene assays demonstrated that the 13-nucleotide repeat and 4 bp deletion within the same haplotype of intron 8 could regulate alternative splicing. The AS isoform lacks exon 8, and is deduced to contain 49 amino acid changes in the membrane-distal portion of the extracellular domain, where considerable amino acid changes are known in CD72callele associated with murine SLE. These results indicated that the presence of CD72-*2 allele decreases risk for human SLE conferred by FCGR2B-232Thr, possibly by increasing the AS isoform of CD72. © Oxford University Press 2004; all rights reserved.